Sailing through the Waves: The Lived Experiences of Working Students Amid Covid-19 - Colet, Maverick Kaypee A.; Javarro, Christy E.; Bautista, Juliny Grace F.; Ormita, Ricah Mae (Jurnal Pendidikan Indonesia Gemilang, 2024)
Being a working student is challenging as they must balance school and work responsibilities. This study aimed to explore the lived experiences of working students in a private higher education institution in the province of La Union, Philippines, during COVID-19. The study is qualitative research, specifically descriptive phenomenology. A purposive sampling technique was used for the selection of participants. A semi-structured interview was used to generate data from 10 participants. Further, thematic analysis was utilized where three major themes emerged: (1) Experiencing the Tidal Rise and Fall of Work-Study Balance, (2) Anchored Expectations and Pressure, and (3) Coping Up and Sailing with the Wind. Ethics were strictly observed in the study. The study revealed that their circumstances form valuable experiences as young adults as they learn to become responsible individuals. They cope by making the necessary adjustments to their schedule, perspective, self-management skills, and formation of support they get from people. They continue the odyssey with burning motivation to strike a work-study balance, hence, highly commendable.